INTERNAL FACTORS AFFECTING ONLINE LEARNING ACCORDING TO STUDENT REFLECTION - Saverina Nungky Dian Hapsari; Heppi Vanadian (Faculty of Medicine Universitas Kristen Duta Wacana, 2022)
Background The COVID-19 pandemic has changed many aspects of life worldwide, including medical education. Offline learning is being replaced by online to reduce the spread of disease through direct contact between the academic community. Along with technological developments, online learning is likely to continue even after the COVID-19 pandemic is over. Therefore, students must be able to adapt and prepare for the next online learning. The preparation can be started by self-assessing the online learning that has been followed so far and finding things that must be improved in future online learning.Objective To explore the student’s performance during online learning.Methods This research was qualitative research using the reflection writings of 156 students regarding their performance during online learning, which would be analyzed according to the depth and content of the reflection.Results Internal factors that support (strengths) and internal factors that inhibit online learning (weaknesses) through student reflection during online learning were found in this study. Internal factors such as maintaining health, self-management, adapting, and maintaining motivation can be maintained to support online learning. Internal factors such as anxiety, avoiding interaction, laziness, failure in time management, and inappropriate learning methods hindered online learning.Conclusion Students can strengthen internal factors that support online learning and reduce internal factors that hinder online learning to optimize online learning in the future.